Development of Interactive E-Modules with STEM-PBL Approach on Ecology and Biodiversity to Improve Critical Thinking Skills and Student Learning Outcomes - Imberd Rionard Liunima; Ellianawati; Arif Widiyatmoko (Jurnal Penelitian Pendidikan IPA, 2025)
The development of Interactive E-Modules with STEM-PBL approach on Ecology and biodiversity materials is needed because of the lack of use of Interactive E-Modules in schools, as well as low critical thinking skills, and student learning outcomes.  This study aims to present the characteristics, validity, effectiveness and relationship of critical thinking skills and student learning outcomes. The results of questionnaire analysis using Aiken-V showed that the E-Module was valid from 5 validators, namely material and media experts with an average value of 0.88. The results of students' critical thinking skills are shown by the N-Gain value of 0.58 with moderate. Student learning outcomes are shown by the N-Gain value of 0.57 with a moderate category.  Based on the results of this study, it can be concluded that the Interactive E-Module with STEM-PBL approach on ecology and biodiversity material can be used in learning to improve students' critical thinking skills and learning outcomes.